Blended Learning Dalam Menghadapi Era Society 5.0 - Irwansyah Suwahyu; Nurul Fajriani Rasid; Yasin Anil Hakim Gobel; Ainun Zahra Adistia; Muttaqia Muttaqia (Jurnal Pendidikan Terapan, 2023)
Society 5.0 is an idea and concept that brings major changes in solving societal problems by utilizing technology and  taking into account human and humanities aspects. At this time, the use of technology such as the internet and e-learning has been effectively used in higher education, one of which is blended learning.  The purpose of this study was to find out how much influence the  use of SYAM-OK has  on blended learning  on the UNM campus. In this study using quantitative methods with Google Form instruments that are distributed online. The sample for this study was active students of  the UNM campus (Students who  use SYAM OK), as  many as 79 respondents who participated in this study. The results of this study are; (1) online learning  using blended learning can affect student  learning outcomes  ;  (2)  the online learning process  based on blended learning  is fairly effective as seen from only 10 respondents / students with an average of 1.3% who do not understand the concept of  blended learning